2019
DOI: 10.18280/acsm.430510
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Al 6061/Al2O3/Fly-Ash Composite Fabricated Through Stir Casting

Abstract: The fly-ash produced in thermal power plants is a major pollutant to the air and soil. This paper designs a new composite material with the fly-ash as the reinforcement. For the composite, the AA 6061 aluminum alloy was taken as the matrix, Al2O3 as the primary reinforcement, and fly-ash as the secondary reinforcement. The microstructure and mechanical properties of the proposed composite were measured, and compared with those of previous experiments on AA 6061 alloy. The results show that the proposed composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 23 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…In addition to the uniform dispersal of the fly ash and carbonized eggshell particles, the improvement in tensile strength is brought about by transferring the load from the aluminium matrix to the hybrid reinforcements due to their different elastic constants [26]. The reduction in ductility which has also been reported in [27], [28] was also reported in this investigation as being a result of the reinforcing phases present in the aluminium matrix.…”
Section: Mechanical Properties and Densitysupporting
confidence: 73%
“…In addition to the uniform dispersal of the fly ash and carbonized eggshell particles, the improvement in tensile strength is brought about by transferring the load from the aluminium matrix to the hybrid reinforcements due to their different elastic constants [26]. The reduction in ductility which has also been reported in [27], [28] was also reported in this investigation as being a result of the reinforcing phases present in the aluminium matrix.…”
Section: Mechanical Properties and Densitysupporting
confidence: 73%
“…It was observed that negligible amount of weight loss was observed for the prepared composite [35,36]. After reinforcing TiC and GS particles, weight loss of the composite dipped in NaCl solution was reduced.…”
Section: Corrosion Analysismentioning
confidence: 95%
“…Mechanical properties like ultimate tensile strength and yield strength are also amplified in the composites, when wt.% of the MoS 2 is increased. 12,13 Rahimian et al 14 have described that the compressive strength is augmented with decreased particle size. Narayanasamy and Selvakumar 15 demarcated that compressive strength of a composite is amplified by the increase in the wt.…”
Section: Introductionmentioning
confidence: 99%